RIFM fragrance ingredient safety assessment, p-tolualdehyde, CAS Registry Number 104-87-0. (March 2021) - Api, A.M.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; et al.
Abstract: The existing information supports the use of this material as described in this safety assessment. p -Tolualdehyde was evaluated for genotoxicity, repeated dose toxicity, developmental and reproductive toxicity, local respiratory toxicity, phototoxicity, skin sensitization potential, and environmental safety. Data from read-across analog benzaldehyde (CAS # 100-52-7) show that p- tolualdehyde is not expected to be genotoxic. Data from read-across analog cuminaldehyde (CAS # 122-03-2) provided p- tolualdehyde a No Expected Sensitization Induction Level (NESIL) of 1100 μg/cm 2 for the skin sensitization endpoint. The repeated dose toxicity, developmental and reproductive toxicity, and local respiratory toxicity endpoints were completed using the threshold of toxicological concern (TTC) for a Cramer Class I material, and the exposure to p- tolualdehyde is below the TTC (0.03 mg/kg/day, 0.03 mg/kg/day, and 1.4 mg/day, respectively). The phototoxicity/photoallergenicity endpoints were evaluated based on data from read-across analog 4-ethylbenzaldehyde (CAS # 4748-78-1); p- tolualdehyde is not expected to be phototoxic/photoallergenic. The environmental endpoints were evaluated; p -tolualdehyde was found not to be persistent, bioaccumulative, and toxic (PBT) as per the International Fragrance Association (IFRA) Environmental Standards, and its risk quotients, based on its current volume of use in Europe and North America (i.e., Predicted Environmental Concentration/Predicted No Effect Concentration [PEC/PNEC]), are <1. Highlights: p -Tolualdehyde; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.